PEREMPUAN DAN KEMATIAN: DEKONSTRUKSI DALAM CERPEN APPOINTMENT IN SAMARRA KARYA W. S. MAUGHAM - Rahmat Setiawan; Sri Nurhidayah (Balai Bahasa Provinsi Jawa Timur, 2019)
William Somerset Maugham's short story “The Appointment in Samarra” (1933) narrates a theme of how someone cannot avoid death, but the death is represented through a female figure. The research aims to expose a critic toward the representation of death through female character which is a cultivation of patriarchal ideas through literary works. This research used deconstruction framework as a reference to expose the paradox between woman and death. This was a qualitative research with an intertextuality approach. The data were in the form of quotations in the text and the source of the data was William Somerset Maugham’s short story “The Appointment in Samarra”. The data were collected through documentation technique and analysed with interpretation method. The results showed that the representation of death through woman was a patriarchal discourse and, with deconstructive reading, the narrative presented a paradoxical side; on one side, it presented that woman had horrible character, but on the other side, the horrible character implied power. Dismantling of the patriarchal discourse made the decon-structive process in this text became study of feminist deconstruction.